Hadith #2994 - Sunan Abi Dawud - Amr bin Abi 'Amr; Anas ibn Malik; Sa'id bin Mnswr bin Sh'bh سعيد بن منصور بن شعبة (Sunan Abi Dawud)
A’ishah said “Safiyyah was called after the word safi (a special portion of the Prophet).”
Grade: Sahih

Hadith #3327 - Sunan Abi Dawud - Abdul 'Aziz bin Muhammad al-Daruradi عبد العزيز بن محمد الدراوردي; Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Amr bin Abi 'Amr; ibn Abbas; Ikrama عكرمة (Sunan Abi Dawud)
“Lying and swearing have a place on i.” ‘Abd Allah al-Zuhri said: “Unprofitable speech and lying.”
Grade: Sahih

Hadith #3570 - Sunan Abi Dawud - Abu Hurairah; Amr bin Abi 'Amr; Fdyl bin Sulaiman al-Nmyry فضيل بن سليمان النميري; Nasr bin 'Ali bin Nasr bin 'Ali; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
Al-Bara’ had a she-camel which was accustomed to graze the standing crop belonging to the people. She entered a garden and did damage to it. The Messenger of Allah (ﷺ) was informed about it. So he gave decision that the owners of gardens are responsible for guarding them by day, and the owners of the animals are responsible for guarding them by night. Any damage done by animals during the night is a responsibility lying on their owners.
Grade: Sahih

Hadith #4460 - Sunan Abi Dawud - Abdul 'Aziz bin Muhammad al-Daruradi عبد العزيز بن محمد الدراوردي; Amr bin Abi 'Amr; ibn Abbas; Ikrama عكرمة (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) made a decision about a man who had intercourse with his wife’s slave-girl as follows. If he forced her, she is free, and he shall give her mistress a slave-girl similar to her; if she asked him to have intercourse voluntarily, she will belong to him, and he shall give her mistress a slave-girl similar to her. Abu Dawud said: This tradition has been transmitted by Yunus b. ‘Ubaid, ‘Amr b. Dinar, Mansur b. Zadhan and Salam from al-Hasan to the same effect. But y
Grade: Hasan

Hadith #4462 - Sunan Abi Dawud - Abdul 'Aziz bin Muhammad al-Daruradi عبد العزيز بن محمد الدراوردي; Abu Ja'far al-Nafaili عبد الله بن محمد أبو جعفر النفيلي الحران; Amr bin Abi 'Amr; ibn Abbas; Ikrama عكرمة (Sunan Abi Dawud)
The Prophet (ﷺ) said: If you find anyone doing as Lot’s people did, kill the one who does it, and the one to whom it is done. Abu Dawud said: A similar tradition has also been transmitted by Sulaiman b. Bilal from ‘Amr b. Abi ‘Umar. And ‘Abbad b. Mansur transmitted it from ‘Ikrimah on the authority of Ibn ‘Abbas who transmitted it from the Prophet (ﷺ). It has also been transmitted by Ibn Juraij from Ibrahim from Dawud b. Al-Husain from ‘Ikrimah on the authority of Ibn ‘Abbas
Grade: Hasan Sahih

Hadith #5190 - Sunan Abi Dawud - Abdul 'Aziz bin Muhammad al-Daruradi عبد العزيز بن محمد الدراوردي; Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Amr bin Abi 'Amr; Ikrama عكرمة (Sunan Abi Dawud)
The Prophet (ﷺ) said: When one of you is invited to take meals and comes along with the messenger, that serves as permission for him to enter. Abu ‘Ali al-Lu’lu said: I heard Abu Dawud say: Qatadah did not hear anything from Abu Rafi’.
Grade: Sahih